Kimura disease: A rare cause of cervical lymphadenopathy and a diagnostic challenge - Virendra Kumar Goyal; Jagdish Vishnoi; Ruhi Dak; Shokat Ali Bohra; Gunjan Sharma (Indian Journal of Allergy Asthma and Immunology)
Kimura disease (KD) is a rare chronic inflammatory disorder characterized by multiple painless solitary head and neck lymphadenopathy often accompanied by peripheral eosinophilia and elevated serum IgE levels. Initially, the lesion was described in 1937 as a neoplasm (Kimm and Szeto) and first coined by Kimura, a Japanese scientist. Now it is well documented that it is a benign condition with unknown etiology. An allergic reaction and an alteration of the immune system remains one of the pathophysiological bases. Persistent antigenic stimulation following arthropod bites and parasitic or candida infection are also suspected. KD is a quite rare condition, affected Caucasians are very rare. It is found almost exclusively in Asian males in their 2nd to 4th decade of life (70–80%). There are only few cases of KD reported from Indian subcontinent. We present a case series of three patients of Kimura disease, presenting with painless cervical and parotid lymphadenopathy. All three patients underwent lymph node fine needle aspiration cytology (FNAC) showing no evidence of malignancy. This case series highlights the very rare yet important cause of cervical lymphadenopathy in young patients. Cervical lymphadenopathy can be misleading if not evaluated by histopathology and serum IgE levels.